Sosialisasi Penerapan Nilai-nilai Pancasila pada Siswa Sekolah Dasar : Studi Kasus pada SD Harapan 212 - Fathiyah Al Khairiyyah; Meivira Ashifa Nanda Herdian; Nada Balqis Tsabitah; Maulia Depriya Kembara4 (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
This study aims to understand the implementation of Pancasila ini SD Harapan 212. The research method employed is qualitative, utilizing direct observation and structured interviews. Participants consist of fourth-grade students at SD Harapan 212 and their class guardians. The results of the study indicate that the implementation of Pancasila values among fourth-grade students at SD Harapan 212 still needs to be improved, particularly in achieving a deeper understanding and application of these values in daily life. This research provides insights into efforts that can be made to enhance the effectiveness of teaching Pancasila values in the school.